Hvad er mesterværker? Kunsten som genforhandling af virkeligheden - Schultz, Laura Luise (Kvinder, Køn & Forskning, 2006)
This article discusses how the idea of a national list of canonical works of art is at odds with performative strategies in contemporary art as they have developed since the early avantgardes first began to mix art and everyday life. From the middle of the 20th century, performative art forms such as happening, body art and all sorts of peformance art and theatre, challenged the notion of the work of art in favor of a concept of art as event or practice. Through the work of American modernist poet Gertrude Stein, and especially her deconstruction of the concepts of masterpieces and genius, the article explores how the performative turn has changed the way art is inscribed in a larger cultural context and history: Significant works of art no longer claim their right to glory through their monumental permanence and significance, but through their ability to change: to relate to shifting perspectives on an ever-changing reality.